How Ethics Affect Business - Zainab Moosa AlAali; Ruth Johanna Powosino; Andre Stevian Muskita (AIBPM Publisher, 2018)
This paper shows the impact of ethics on business, where ethics are divided into several sections, including personal ethics, social ethics, religious and professional ethics. This research will focus on ethics policy in business and the importance of imposing it on employees and managers in the companies. Followed by the results of their application to employees and customers. This research employs a descriptive methodology, using literature studies as source of theories. The study case is taken in a Nissan company based in Japan.